Cognitive training in children with hypoplastic left heart syndrome: A pilot randomized trial. (June 2020) - Jordan, Lori C.; Siciliano, Rachel E.; Cole, David A.; Lee, Chelsea A.; Patel, Niral J.; Murphy, Lexa K.; Markham, Larry W.; Prussien, Kemar V.; Gindville, Melissa C.; Compas, Bruce E.
Abstract: Neurodevelopmental disabilities are common sequelae of congenital heart disease, particularly cognitive impairments that impede academic achievement. Cognitive training has been shown to be effective in improving working memory in other patient groups. Computerized cognitive training programs may hold potential for children and adolescents with congenital heart disease, but are untested in this population. In this single-center, single-blinded, randomized controlled trial, the feasibility and efficacy of Cogmed Working Memory Training (Cogmed) was compared with observation in children with hypoplastic left heart syndrome 8 to 16 years of age. Participants were randomized to either Cogmed at home for 5 weeks with coaching by a study team member or an observation control group. Baseline, 6–8 weeks later (post-intervention), and 6-month assessments of working memory were completed. Participants randomized to the Cogmed intervention (n = 10) demonstrated greater improvement than controls (n = 10) on measures of working memory, the Wechsler Intelligence Scale for Children-V Working Memory Index and the National Institutes of Health Toolbox Cognitive Battery post-training that were statistically significant (Cohen's d  = 0.76, p  < .001 and d  = 0.43, p  < .01) compared to controls over the same time period. Improvements were not maintained at 6-month follow-up. Three children withdrew from cognitive training, and one additional child did not complete at least 20 of 25 cognitive training sessions despite coaching. In conclusion, study findings show computerized cognitive training is feasible for most children with hypoplastic left heart syndrome, but shorter sessions may improve adherence. Training-related improvements in working memory occur, though continued reinforcement may be necessary for these gains to be maintained. Highlights: Cognitive impairments are common sequelae of congenital heart disease. Cognitive training programs have potential for children with congenital heart disease. Improvements in working memory were shown immediately following cognitive training. Improvements in working memory (WM) were not sustained over time. Continued reinforcement may be necessary for these gains in WM to be maintained.